Anodal tDCS does not enhance the learning of the sequential finger-tapping task by motor imagery practice in healthy older adults - Metais, Angèle; Muller, Camille O.; Boublay, Nawale; Breuil, Caroline; Guillot, Aymeric; Daligault, Sébastien; Di Rienzo, Franck; Collet, Christian; Krolak-Salmon, Pierre; Saimpont, Arnaud (Frontiers in Aging Neuroscience, 2022)
Background. Motor imagery practice (MIP) and anodal transcranial direct current stimulation (a-tDCS) are innovative methods with independent positive influence on motor sequence learning (MSL) in older adults. Objective. The present study investigated the effect of MIP combined with a-tDCS over the primary motor cortex (M1) on the learning of a finger tapping sequence of the non-dominant hand in healthy older adults. Methods. Thirty participants participated in this double-blind sham-controlled study. They performed three MIP sessions, one session per day over three consecutive days and a retention test one week after the last training session. During training / MIP, participants had to mentally rehearse an 8-element finger tapping sequence with their left hand, concomitantly to either real (a-tDCS group) or sham stimulation (sham-tDCS group). Before and after MIP, as well as during the retention test, participants had to physically perform the same sequence as fast and accurately as possible. Results. Our mains results showed that both groups i) improved their performance during the first two training sessions, reflecting acquisition / on-line performance gains, ii) stabilized their performance from one training day to another, reflecting off-line consolidation; as well as after seven days without practice, reflecting retention, (iii) for all stages of MSL, there was no significant difference between the sham-tDCS and a-tDCS groups. Conclusion. This study highlights the usefulness of MIP in motor sequence learning for older adults. However, 1.5mA a-tDCS did not enhance the beneficial effects of MIP, which adds to the inconsistency of results found in tDCS studies. Future work is needed to further explore the best conditions of use of tDCS to improve motor sequence learning with MIP.